Rock plate with flash crystal effect and preparation method thereof
By using glaze modification materials on ceramic rock slabs, combining modified translucent stone agents and strontium carbonate modifiers, the contradiction between the flash crystal effect of existing rock slabs and the anti-fouling and easy-to-clean properties has been solved, and better results have been achieved flash crystal effect and use efficiency.
Patent Information
- Application Number
- CN202411505870.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-28
AI Technical Summary
In order to improve the flash crystal effect, the glaze layer of existing ceramic rock slabs has poor anti-fouling and easy cleaning performance, and poor scrubbing and alkali corrosion resistance, which limits the efficiency of the product.
The glaze modified materials include potassium feldspar, calcium oxide, barium oxide and cobalt oxide. By adding modified translucent lithologic agent and strontium carbonate modifier to form a flash crystal effect. Glaze modified layer.
It improves the flash crystal effect of the rock slab, and at the same time enhances the anti-fouling and easy cleaning performance, improving the product's scrubbing resistance and alkali corrosion resistance stability.
Smart Images

Figure SMS_6 
Figure SMS_7
Abstract
Description
Technical Field
[0001] This invention relates to the field of sintered stone technology, specifically to a sintered stone with a shimmering effect and its preparation method. Background Art
[0002] Ceramic slabs have become increasingly popular in the market due to their high strength, hardness, and decorative appeal. They can be used not only for conventional wall and floor decorations but also for countertops, cabinet doors, drawer doors, screens, and more.
[0003] The glaze used in existing sintered stone slabs, in order to improve the shimmering effect, tends to have poor stain resistance and easy cleaning properties. At the same time, the products have poor scrubbing resistance and alkali corrosion stability, which further limits the efficiency of product use. Summary of the Invention
[0004] In view of the deficiencies of the prior art, the purpose of this invention is to provide a rock slab with a shimmering effect and a method for preparing the same, so as to solve the problems mentioned in the background art.
[0005] The present invention solves the technical problem by adopting the following technical solutions: This invention provides a slab with a shimmering effect. The slab includes a blank layer, and a glaze modifier is applied to the surface of the blank layer to form a glaze modifier layer. The glaze modifier comprises the following raw materials in parts by weight: Potassium feldspar 5-8 parts, calcined talc powder 4-7 parts, modified translucent stone agent 3-5 parts, calcium oxide 3-5 parts, barium oxide 2-4 parts, cobalt oxide 1-3 parts, strontium carbonate modifier 2-4 parts.
[0006] Preferably, the glaze modifier comprises the following raw materials in parts by weight: Potassium feldspar 6.5 parts, calcined talc powder 5.5 parts, modified translucent stone agent 4 parts, calcium oxide 4 parts, barium oxide 3 parts, cobalt oxide 2 parts, strontium carbonate modifier 3 parts.
[0007] Preferably, the modified translucent stone agent is prepared by: S1: Irradiate the translucent stone in a proton irradiation chamber for 5-10 minutes at 350-400W. After irradiation, the irradiated translucent stone is obtained. S2: Add 3-5 parts of wollastonite and 1-3 parts of carboxymethyl cellulose to 5-8 parts of sodium dodecylbenzenesulfonate solution, and then add 1-2 parts of silane coupling agent KH560. Mix thoroughly to obtain wollastonite agent. S2: The irradiated translucent stone and wollastonite agent are mixed at a weight ratio of 5:3 and ball-milled at a speed of 1000-1500 r / min for 1 hour. After ball milling, the mixture is washed with water and dried to obtain the modified translucent stone agent.
[0008] Preferably, the sodium dodecylbenzenesulfonate solution has a mass fraction of 2-5%.
[0009] Preferably, the strontium carbonate modifier is prepared by: S11: Strontium carbonate and sodium lignosulfonate solution are mixed at a weight ratio of 2:5 to obtain strontium carbonate solution; S12: Add the modified nano zinc oxide to the yttrium nitrate solution at a weight ratio of 4:7 and stir until well mixed to obtain nano zinc solution; S13: Mix strontium carbonate solution and nano zinc solution at a weight ratio of 5:2 and ball mill them at a speed of 500-1000 r / min for 2 hours. After ball milling, wash with water and dry to obtain strontium carbonate modifier.
[0010] Preferably, the sodium lignosulfonate solution has a mass fraction of 2-5%; and the yttrium nitrate solution has a mass fraction of 3-6%.
[0011] Preferably, the modified nano zinc oxide is prepared by: The modified solution is prepared by mixing 2-4 parts urea, 1-3 parts lanthanum chloride solution and 2-4 parts sodium silicate solution evenly. The modified nano zinc oxide is obtained by heat-treating the nano zinc oxide at 65-75℃ for 5-10 minutes, then spraying the surface with a modification liquid to wet the surface, and finally washing and drying it with water.
[0012] By using nano-zinc oxide and a modified liquid for synergistic formulation, it can better complement strontium carbonate solution, thereby further improving the product's performance.
[0013] Preferably, the lanthanum chloride solution has a mass fraction of 2-5%; and the sodium silicate solution has a mass fraction of 4-7%.
[0014] This invention also provides a method for preparing a slab with a shimmering effect, comprising the following steps: wet ball milling the raw materials in the glaze modifier for 1-2 hours at a ball milling speed of 1000 r / min; after ball milling, the glaze modifier is obtained; the glaze modifier is applied to the body layer, and the amount of glaze applied is... Finally, the sintering temperature is 1250℃ for 50-60 minutes. After sintering, a rock slab with a shimmering effect is obtained.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The slab with a shimmering effect of this invention is made by applying a glaze modifier. The glaze modifier uses potassium feldspar, calcined talc, calcium oxide, barium oxide, and cobalt oxide as the matrix. By adding strontium carbonate modifier and translucent stone modifier, the two work together to enhance the effect. The resulting glaze modifier improves the shimmering effect of the product and enhances its stain resistance and easy-to-clean properties. At the same time, the product shows significant improvements in scrub resistance and alkali corrosion resistance. The translucent stone modifier is made by proton irradiation of translucent stone to optimize its activity. It is then further improved by wollastonite agent, resulting in further enhanced product performance. In addition, the translucent stone modifier can further synergize with the strontium carbonate modifier, thus further improving the product performance. Detailed Implementation
[0016] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0017] This embodiment provides a slab with a shimmering effect. The slab includes a blank layer, and a glaze modifier is applied to the surface of the blank layer to form a glaze modifier layer. The glaze modifier includes the following raw materials in parts by weight: Potassium feldspar 5-8 parts, calcined talc powder 4-7 parts, modified translucent stone agent 3-5 parts, calcium oxide 3-5 parts, barium oxide 2-4 parts, cobalt oxide 1-3 parts, strontium carbonate modifier 2-4 parts.
[0018] The glaze modifier in this embodiment comprises the following raw materials in parts by weight: Potassium feldspar 6.5 parts, calcined talc powder 5.5 parts, modified translucent stone agent 4 parts, calcium oxide 4 parts, barium oxide 3 parts, cobalt oxide 2 parts, strontium carbonate modifier 3 parts.
[0019] The preparation method of the modified translucent stone agent in this embodiment is as follows: S1: Irradiate the translucent stone in a proton irradiation chamber for 5-10 minutes at 350-400W. After irradiation, the irradiated translucent stone is obtained. S2: Add 3-5 parts of wollastonite and 1-3 parts of carboxymethyl cellulose to 5-8 parts of sodium dodecylbenzenesulfonate solution, and then add 1-2 parts of silane coupling agent KH560. Mix thoroughly to obtain wollastonite agent. S2: The irradiated translucent stone and wollastonite agent are mixed at a weight ratio of 5:3 and ball-milled at a speed of 1000-1500 r / min for 1 hour. After ball milling, the mixture is washed with water and dried to obtain the modified translucent stone agent.
[0020] The sodium dodecylbenzenesulfonate solution in this embodiment has a mass fraction of 2-5%.
[0021] The preparation method of the strontium carbonate modifier in this embodiment is as follows: S11: Strontium carbonate and sodium lignosulfonate solution are mixed at a weight ratio of 2:5 to obtain strontium carbonate solution; S12: Add the modified nano zinc oxide to the yttrium nitrate solution at a weight ratio of 4:7 and stir until well mixed to obtain nano zinc solution; S13: Mix strontium carbonate solution and nano zinc solution at a weight ratio of 5:2 and ball mill them at a speed of 500-1000 r / min for 2 hours. After ball milling, wash with water and dry to obtain strontium carbonate modifier.
[0022] In this embodiment, the sodium lignosulfonate solution has a mass fraction of 2-5%; the yttrium nitrate solution has a mass fraction of 3-6%.
[0023] The preparation method of the modified nano zinc oxide in this embodiment is as follows: The modified solution is prepared by mixing 2-4 parts urea, 1-3 parts lanthanum chloride solution and 2-4 parts sodium silicate solution evenly. The modified nano zinc oxide is obtained by heat-treating the nano zinc oxide at 65-75℃ for 5-10 minutes, then spraying the surface with a modification liquid to wet the surface, and finally washing and drying it with water.
[0024] In this embodiment, the lanthanum chloride solution has a mass fraction of 2-5%; the sodium silicate solution has a mass fraction of 4-7%.
[0025] This embodiment describes a method for preparing a slab with a shimmering effect, comprising the following steps: wet ball milling the raw materials in the glaze modifier for 1-2 hours at a milling speed of 1000 r / min; after milling, the glaze modifier is obtained; the glaze modifier is then applied to the body layer, with an application amount of [missing information]. Finally, the sintering temperature is 1250℃ for 50-60 minutes. After sintering, a rock slab with a shimmering effect is obtained.
[0026] Example 1. This embodiment provides a slab with a shimmering effect. The slab includes a blank layer, and a glaze modifier is applied to the surface of the blank layer to form a glaze modifier layer. The glaze modifier includes the following raw materials in parts by weight: Five parts potassium feldspar, four parts calcined talc powder, three parts modified translucent stone agent, three parts calcium oxide, two parts barium oxide, one part cobalt oxide, and two parts strontium carbonate modifier.
[0027] The preparation method of the modified translucent stone agent in this embodiment is as follows: S1: Irradiate the translucent stone in a proton irradiation chamber for 5 minutes at 350W. After irradiation, the irradiated translucent stone is obtained. S2: Add 3 parts wollastonite and 1 part carboxymethyl cellulose to 5 parts sodium dodecylbenzene sulfonate solution, then add 1 part silane coupling agent KH560 and mix thoroughly to obtain wollastonite agent; S2: The irradiated translucent stone and wollastonite agent are mixed at a weight ratio of 5:3 and ball-milled at a speed of 1000 r / min for 1 hour. After ball milling, the mixture is washed with water and dried to obtain the modified translucent stone agent.
[0028] The sodium dodecylbenzenesulfonate solution in this embodiment has a mass fraction of 2%.
[0029] The preparation method of the strontium carbonate modifier in this embodiment is as follows: S11: Strontium carbonate and sodium lignosulfonate solution are mixed at a weight ratio of 2:5 to obtain strontium carbonate solution; S12: Add the modified nano zinc oxide to the yttrium nitrate solution at a weight ratio of 4:7 and stir until well mixed to obtain nano zinc solution; S13: Strontium carbonate solution and nano zinc solution are mixed at a weight ratio of 5:2 and ball-milled at a speed of 500 r / min for 2 hours. After ball milling, the mixture is washed with water and dried to obtain strontium carbonate modifier.
[0030] In this embodiment, the sodium lignosulfonate solution has a mass fraction of 2%; the yttrium nitrate solution has a mass fraction of 3%.
[0031] The preparation method of the modified nano zinc oxide in this embodiment is as follows: The modified solution was obtained by mixing 2 parts urea, 1 part lanthanum chloride solution and 2 parts sodium silicate solution evenly. The modified nano zinc oxide is obtained by heat-treating the nano zinc oxide at 65℃ for 5 minutes, then spraying the surface with a modification liquid to wet the surface, and finally washing and drying it with water.
[0032] In this embodiment, the lanthanum chloride solution has a mass fraction of 2%; the sodium silicate solution has a mass fraction of 4%.
[0033] This embodiment describes a method for preparing a slab with a shimmering effect, comprising the following steps: wet ball milling the raw materials in the glaze modifier for 1 hour at a milling speed of 1000 r / min; after milling, the glaze modifier is obtained; the glaze modifier is then applied to the body layer, with an application amount of [missing information]. Finally, the sintering temperature was 1250℃ for 50 minutes, and the sintering was completed to obtain a rock slab with a shimmering effect.
[0034] Example 2. This embodiment provides a slab with a shimmering effect. The slab includes a blank layer, and a glaze modifier is applied to the surface of the blank layer to form a glaze modifier layer. The glaze modifier includes the following raw materials in parts by weight: 8 parts potassium feldspar, 7 parts calcined talc powder, 5 parts modified translucent stone agent, 5 parts calcium oxide, 4 parts barium oxide, 3 parts cobalt oxide, and 4 parts strontium carbonate modifier.
[0035] The preparation method of the modified translucent stone agent in this embodiment is as follows: S1: Irradiate the translucent stone in a proton irradiation chamber for 10 minutes at 400W. After irradiation, the irradiated translucent stone is obtained. S2: Add 5 parts wollastonite and 3 parts carboxymethyl cellulose to 8 parts sodium dodecylbenzene sulfonate solution, then add 2 parts silane coupling agent KH560 and mix thoroughly to obtain wollastonite agent; S2: The irradiated translucent stone and wollastonite agent are mixed at a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 hour. After ball milling, the mixture is washed with water and dried to obtain the modified translucent stone agent.
[0036] The sodium dodecylbenzenesulfonate solution in this embodiment has a mass fraction of 5%.
[0037] The preparation method of the strontium carbonate modifier in this embodiment is as follows: S11: Strontium carbonate and sodium lignosulfonate solution are mixed at a weight ratio of 2:5 to obtain strontium carbonate solution; S12: Add the modified nano zinc oxide to the yttrium nitrate solution at a weight ratio of 4:7 and stir until well mixed to obtain nano zinc solution; S13: Strontium carbonate solution and nano zinc solution are mixed at a weight ratio of 5:2 and ball-milled at a speed of 1000 r / min for 2 hours. After ball milling, the mixture is washed with water and dried to obtain strontium carbonate modifier.
[0038] In this embodiment, the sodium lignosulfonate solution has a mass fraction of 5%; the yttrium nitrate solution has a mass fraction of 6%.
[0039] The preparation method of the modified nano zinc oxide in this embodiment is as follows: The modified solution was obtained by mixing 4 parts urea, 3 parts lanthanum chloride solution and 4 parts sodium silicate solution evenly. The modified nano zinc oxide is obtained by heat-treating the nano zinc oxide at 75℃ for 10 minutes, then spraying the surface with a modification liquid to wet the surface, and finally washing and drying it with water.
[0040] In this embodiment, the lanthanum chloride solution has a mass fraction of 5%; the sodium silicate solution has a mass fraction of 7%.
[0041] This embodiment describes a method for preparing a slab with a shimmering effect, comprising the following steps: wet ball milling the raw materials in the glaze modifier for 2 hours at a speed of 1000 r / min; after ball milling, the glaze modifier is obtained; the glaze modifier is then applied to the body layer, with an application amount of [missing information]. Finally, the sintering temperature was 1250℃ for 60 minutes, and the sintering was completed to obtain a rock slab with a shimmering effect.
[0042] Example 3. This embodiment provides a slab with a shimmering effect. The slab includes a blank layer, and a glaze modifier is applied to the surface of the blank layer to form a glaze modifier layer. The glaze modifier includes the following raw materials in parts by weight: Potassium feldspar 6.5 parts, calcined talc powder 5.5 parts, modified translucent stone agent 4 parts, calcium oxide 4 parts, barium oxide 3 parts, cobalt oxide 2 parts, strontium carbonate modifier 3 parts.
[0043] The preparation method of the modified translucent stone agent in this embodiment is as follows: S1: Irradiate the translucent stone in a proton irradiation chamber for 7.5 minutes at 370W. After irradiation, the irradiated translucent stone is obtained. S2: Add 4 parts wollastonite and 2 parts carboxymethyl cellulose to 6.5 parts sodium dodecylbenzene sulfonate solution, then add 1.5 parts silane coupling agent KH560 and mix thoroughly to obtain wollastonite agent; S2: The irradiated translucent stone and wollastonite agent are mixed at a weight ratio of 5:3 and ball-milled at a speed of 1250 r / min for 1 hour. After ball milling, the mixture is washed with water and dried to obtain the modified translucent stone agent.
[0044] The sodium dodecylbenzenesulfonate solution in this embodiment has a mass fraction of 3.5%.
[0045] The preparation method of the strontium carbonate modifier in this embodiment is as follows: S11: Strontium carbonate and sodium lignosulfonate solution are mixed at a weight ratio of 2:5 to obtain strontium carbonate solution; S12: Add the modified nano zinc oxide to the yttrium nitrate solution at a weight ratio of 4:7 and stir until well mixed to obtain nano zinc solution; S13: Strontium carbonate solution and nano zinc solution were mixed at a weight ratio of 5:2 and ball-milled at a speed of 750 r / min for 2 hours. After ball milling, the mixture was washed with water and dried to obtain strontium carbonate modifier.
[0046] In this embodiment, the sodium lignosulfonate solution has a mass fraction of 3.5%; the yttrium nitrate solution has a mass fraction of 4.5%.
[0047] The preparation method of the modified nano zinc oxide in this embodiment is as follows: The modified solution was obtained by mixing 3 parts urea, 2 parts lanthanum chloride solution and 3 parts sodium silicate solution evenly. The modified nano zinc oxide is obtained by heat-treating the nano zinc oxide at 70℃ for 7.5 min, then spraying the surface with a modification liquid to wet the surface, and finally washing and drying it with water.
[0048] In this embodiment, the lanthanum chloride solution has a mass fraction of 3.5%; the sodium silicate solution has a mass fraction of 5.5%.
[0049] This embodiment describes a method for preparing a slab with a shimmering effect, comprising the following steps: wet ball milling the raw materials in the glaze modifier for 1.5 hours at a milling speed of 1000 r / min; after milling, the glaze modifier is obtained; the glaze modifier is then applied to the body layer, with an application amount of [missing information]. Finally, the sintering temperature was 1250℃ for 55 minutes, and the sintering was completed to obtain a rock slab with a shimmering effect.
[0050] Comparative Example 1. Unlike Example 3, no modified translucent stone agent was added.
[0051] Comparative Example 2. Unlike Example 3, no wollastonite agent was added in the preparation of the modified translucent stone agent.
[0052] Comparative Example 3. Unlike Example 3, no wollastonite or carboxymethyl cellulose was added to the wollastonite agent.
[0053] Comparative Example 4. Unlike Example 3, no strontium carbonate modifier was added.
[0054] Comparative Example 5. Unlike Example 3, no nano-zinc liquid was added in the preparation of the strontium carbonate modifier.
[0055] Comparative Example 6. Unlike Example 3, no modified nano zinc oxide was added to the nano zinc liquid.
[0056] Comparative Example 7. Unlike Example 3, no modification solution was used in the preparation of the modified nano zinc oxide.
[0057] Performance tests of Examples 1-3 and Comparative Examples 1-7 involved placing the products under a 2% sodium hydroxide alkaline mist environment for 24 hours and then wiping them 10 times with a 5N load. The test results are as follows:
[0058] As can be seen from Comparative Examples 1-7 and Examples 1-3, the product of the present invention can achieve a coordinated improvement in terms of distinct layers, vibrant colors, and stain resistance, while the product also exhibits significant scrub resistance and stability. The product performance deteriorates significantly when either modified translucent stone agent or strontium carbonate modifier is not added. Furthermore, the product performance also deteriorates when either wollastonite or carboxymethyl cellulose is not added during the preparation of the modified translucent stone agent, or when nano-zinc liquid is not added during the preparation of the strontium carbonate modifier, or when modified nano-zinc oxide is not added during the preparation of the nano-zinc oxide, or when a modifying liquid treatment is not used during the preparation of the modified nano-zinc oxide. The product performance is most significantly improved when different methods are used to obtain the raw materials; other methods are not as effective as the results of this invention.
[0059] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
[0060] In addition, it should be understood that although this specification is described in terms of implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.
Claims
1. A rock plate with a scintillating effect, the rock plate comprising a green body layer, characterized in that: A glaze modifier is applied to the surface of the green body layer to form a glaze modifier layer. The glaze modifier includes the following raw materials in parts by weight: 5-8 parts of potassium feldspar, 4-7 parts of burned talc, 3-5 parts of modified translucent stone agent, 3-5 parts of calcium oxide, 2-4 parts of barium oxide, 1-3 parts of cobalt oxide, and 2-4 parts of strontium carbonate modifier.
2. A rock plate with a scintillating effect according to claim 1, characterized in that: The glaze modifier includes the following raw materials in parts by weight: 6.5 parts of potassium feldspar, 5.5 parts of burned talc, 4 parts of modified translucent stone agent, 4 parts of calcium oxide, 3 parts of barium oxide, 2 parts of cobalt oxide, and 3 parts of strontium carbonate modifier.
3. A rock plate with a scintillating effect according to claim 1, characterized in that: The preparation method of the modified light-transmitting stone agent is: S1: irradiate the translucent stone in a proton irradiation box for 5-10 minutes at 350-400W, and obtain irradiated translucent stone after the irradiation is completed; S2: adding 3-5 parts of wollastonite and 1-3 parts of carboxymethyl cellulose to 5-8 parts of sodium dodecylbenzene sulfonate solution, and then adding 1-2 parts of silane coupling agent KH560, and mixing thoroughly to obtain wollastonite agent; S2: The irradiated translucent stone and wollastonite are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain a modified translucent stone agent.
4. A rock plate with a scintillating effect according to claim 3, characterized in that: The mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%.
5. The rock plate with a scintillating effect according to claim 1, characterized in that: The preparation method of the strontium carbonate modifier is: S11: stirring and mixing strontium carbonate and sodium lignin sulfonate solution at a weight ratio of 2:5 to obtain strontium carbonate solution; S12: adding the modified nano zinc oxide into the yttrium nitrate solution in a weight ratio of 4:7 and stirring to obtain a nano zinc solution; S13: mixing strontium carbonate solution and nano zinc solution in a weight ratio of 5:2, and ball milling at a ball milling speed of 500-1000 r / min for 2 h. After the ball milling is completed, washing with water and drying are performed to obtain a strontium carbonate modifier.
6. A rock plate with a scintillating effect according to claim 5, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 2-5%; the mass fraction of the yttrium nitrate solution is 3-6%.
7. The rock plate with a scintillating effect according to claim 5, characterized in that: The preparation method of the modified nano zinc oxide is: 2-4 parts of urea, 1-3 parts of lanthanum chloride solution and 2-4 parts of sodium silicate solution are uniformly mixed to obtain a modified solution; The nano zinc oxide is heat treated at 65-75°C for 5-10 minutes, and then the surface is sprayed with a modification liquid to wet the surface, and finally washed with water and dried to obtain the modified nano zinc oxide.
8. A rock plate with a scintillating effect according to claim 7, characterized in that: The mass fraction of the lanthanum chloride solution is 2-5%; the mass fraction of the sodium silicate solution is 4-7%.
9. A method for preparing a rock plate with a scintillating effect as claimed in any one of claims 1 to 8, characterized in that: The process comprises the following steps: wet ball milling the raw materials in the glaze modification material for 1-2 hours at a ball milling speed of 1000 r / min, obtaining the glaze modification material after the ball milling, and applying the glaze modification material to the body layer at a glaze application amount of Finally, it is sintered at a sintering temperature of 1250°C for 50-60 minutes. After the sintering is completed, a rock plate with a crystalline effect is obtained.
Citation Information
Patent Citations
Light-transmitting stone ceramic plate and preparation method thereof
CN113800879A
Rock plate with multiple colored crystal mutton fat crystal glaze effects and preparation method
CN115124372A
Digital distribution flash crystal effect rock plate and preparation method thereof
CN116332675A
Metal flashing glaze, preparation method thereof and glazed tile
CN117700258A
Metal glittering glazed tile with fine texture
CN117700260A